PENGARUH GOOD CORPORATE GOVERNANCE, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Perdagangan yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017) - Esti Dewi Purwati; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe purpose of this study was to determine the effect of good corporate governance, funding decisions, and dividend policies on the value of the company in trading companies listed on the Indonesia Stock Exchange for the period 2015-2017, namely as many as 62 companies. The sample selection uses a purposive sampling method where samples are taken based on certain criteria, so that 20 trading companies are listed on the Indonesia Stock Exchange in 2015-2017. The data analysis technique in this study uses descriptive analysis, classic assumption test, multiple linear regression test, hypothesis test and coefficient of determination using the SPSN version 14 software. The measurement instrument used to measure good corporate governance is the Independent Board of Commissioners (DKI), for funding decisions is Debt to Equity Ratio (DER), for dividend policy is the Dividend Payout Ratio (DPR), and for company value using Price Earning Ratio (PER). The results of this study indicate that: 1) good corporate governance has a positive and significant influence on firm value. 2) funding decisions have a negative and significant influence on company value. 3) dividend policy has a positive and significant effect on firm value.Keywords: Good Corporate Governance, Funding Decisions, Dividend Policy and Company Value